Association Between Lactic Dehydrogenase-to-Albumin Ratio and Short-Time Mortality in Patients with Chronic Obstructive Pulmonary Disease - Yao X; Xue H; Luo J (International Journal of COPD)
Xiqing Yao, Haoyue Xue, Jiye Luo Emergency Department, The First People’s Hospital of Lianyungang, Lianyungang City, 222006, People’s Republic of ChinaCorrespondence: Jiye Luo, Emergency Department, The First People’s Hospital of Lianyungang, Lianyungang City, 222006, People’s Republic of China, Email luojiyeluojiye500@163.comPurpose: The lactate dehydrogenase-to-albumin ratio (LAR) has emerged as a prognostic marker for critically ill patients, yet its relationship with mortality in chronic obstructive pulmonary disease (COPD) remains poorly understood. Our purpose is to assess the predictive value of LAR in COPD patients.Patients and Methods: In this retrospective cohort study, data were extracted from the MIMIC IV database. COPD patients were divided into two groups based on 28-day all-cause mortality. To investigate the relationship between LAR and short-term mortality, multivariate Cox regression, receiver operating characteristic (ROC) analysis, and Kaplan–Meier survival analysis were performed.Results: The study included 1048 COPD patients, with 37% experiencing 28-day mortality. LAR was identified as an independent predictor of 28-day mortality (hazard ratio [HR] 1.01, 95% confidence interval [CI]: 1.01– 1.01, P < 0.001). ROC analysis showed that LAR had an area under the curve (AUC) of 69.48% (95% CI: 65.67– 73.29%), demonstrating superior discriminatory power compared to lactate dehydrogenase (AUC = 66.69%) or albumin (AUC = 36.88%) alone. Additionally, LAR’s predictive performance was comparable to that of the Simplified Acute Physiology Score II (SAPSII), which yielded an AUC of 76.8% (95% CI: 73.54– 80.06%). COPD patients with high LAR values (> 120) had significantly higher 28-day mortality rates (P < 0.001).Conclusion: Elevated LAR is an independent predictor of 28-day mortality in ICU patients with COPD. LAR proves to be a valuable prognostic tool that may assist in the early identification of high-risk patients with CPPD.Keywords: COPD, lactate dehydrogenase-to-albumin ratio, 28-day all-cause mortality, MIMIC-IV, critically ill